Outcomes of etravirine-based antiretroviral treatment in treatment-experienced children and adolescents living with HIV in Europe and Thailand. Issue 3 (10th June 2022) - European Pregnancy; Paediatric Infections Cohort Collaboration (EPPICC),; Lyons, Alex; Thompson, Lindsay; Chappell, Elizabeth; Ene, Luminita; Galli, Luisa; Goetghebuer, Tessa; Jourdain, Gonzague; Noguera-Julian, Antoni; Kahlert, Christian R; Königs, Christoph; et al.
Background: Etravirine (ETR) is approved as a component of second or third-line antiretroviral treatment (ART) for children living with HIV. We assessed the outcomes of ETR-based ART in children in routine care in Europe and Thailand. Methods: Data on children aged <18 years at ETR start were pooled from 17 observational cohorts. Characteristics at ETR start, immunological and virological outcomes at 12 months, discontinuations, adverse events (AEs) and serious adverse events (SAEs) were described. Follow-up was censored at ETR discontinuation, death or last visit. Results: 177 children ever received ETR. At ETR start, median [IQR] age was 15 [12, 16] years, CD4 count 480 [287, 713] cells/mm 3, 70% had exposure to ≥3 ART classes and 20% had viral load (VL) <50 copies/mL. 95% received ETR in combination with ≥1 potent drug class, mostly protease inhibitor-based regimens. Median time on ETR was 24 [7, 48] months. Amongst those on ETR at 12 months ( n =141), 69% had VL<50 copies/mL. Median CD4 increase since ETR start ( n =83) was 147 [16, 267] cells/mm 3 . Overall, 81 (46%) discontinued ETR by last follow-up. Median time to discontinuation was 23 [8, 47] months. Common reasons for discontinuation were treatment simplification (19%), treatment failure (16%) and toxicity (12%). Eight children (5%) had AEs causally associated with ETR, all dermatological/hypersensitivity reactions. Two were SAEs, both Stevens–Johnson Syndrome in children on regimens containing ETR and darunavir and were causally related to either drugs; both resolved following ART discontinuation. Conclusion: Children receiving ETR were predominantly highly treatment-experienced, over two-thirds were virally suppressed at 12 months.